An electron microscopic study of the natural death of cyst cells in Sarcosporidia. II. Ultrastructural changes in the nuclei of cyst cells of Sarcocystis muris - Radchenko, A I; Beĭer, T V (T͡S︡itologii͡a, 1995)
Nuclear changes in cyst cells, developing within 6 and 10 month old sarcocysts of Sarcocystis muris, were followed in terms of the programmed cell death phenomenon. This communication extends our previous studies in the cytoplasm of S. muris cyst cells (Radchenko et al., 1995) to include particular nuclear changes in different involve changes in nuclear configuration: the original spherical from is progressively substituted for irregular or lobulated shapes. This may suggest some corresponding changes in cytoskeleton, involved in formation and maintaining of some definite nuclear shape. In normal cyst cells, the nuclear chromatin appears as a filiform and reticulate structure with a few lumps made of granules and filaments. In the cyst stages subject to natural cell death, structural changes in nuclei involve disassembly of lumps into separate granules. Some spherical structures are seen outbudding from the nucleolus. These structures are presumably made of RNA-containing granules. The pattern of nucleolar segregation in S. muris cells resembles somewhat the changes in nucleoli reported for metazoan cells. However, the general picture of morphological evolution in the nuclei of S. muris cells, in the course of natural dying, differs from that in metazoan cell nuclei. No condensation of nuclear chromatin at the nuclear periphery, or blebbing of the nuclear and cytoplasmic membranes, so characteristic of the latter, was followed in the former. The peculiarities noticed in the sarcosporidia may reflect biological peculiarities of these specialized parasitic protozoa.